2005
DOI: 10.1590/s1516-635x2005000300004
|View full text |Cite
|
Sign up to set email alerts
|

Methionine sources do not affect performance and carcass yield of broilers fed vegetable diets and aubmitted to cyclic heat stress

Abstract: The supplementation of vegetal diets with L-methionine (100% molar), methionine hydroxyl analogue (HMB) (88% molar) or DLmethionine (99% molar) was compared as to the performance of broilers allocated in cages and submitted to cyclic heat stress (CHS). The trial was carried out from 21 to 42 days of age. Two levels of synthetic methionine were supplemented for each methionine source (0.1 or 0.3 %), and the control treatment was not supplemented with synthetic methionine (negative control). Statistical analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…Methionine is considered an essential amino acid for meat production and development (Liu et al, 2010). Consistent results were reported by other authors (Esteve-Garcia & Liaurado, 1997;Ribeiro et al, 2005;Bunchasak et al, 2006). A significant effect of NaCl level (p<0.05) was observed, with the level of 6.0 g/kg promoting higher carcass, leg, and breast weights (Table 4).…”
Section: Effects Of Methionine Source Arginine:lysine Ratio and Sodisupporting
confidence: 70%
“…Methionine is considered an essential amino acid for meat production and development (Liu et al, 2010). Consistent results were reported by other authors (Esteve-Garcia & Liaurado, 1997;Ribeiro et al, 2005;Bunchasak et al, 2006). A significant effect of NaCl level (p<0.05) was observed, with the level of 6.0 g/kg promoting higher carcass, leg, and breast weights (Table 4).…”
Section: Effects Of Methionine Source Arginine:lysine Ratio and Sodisupporting
confidence: 70%
“…The availability of methionine from L-Met, DL-Met and LMA is 100%, 99% and 88%, respectively. L-Met is directly used by the animal as a precursor for protein synthesis and metabolized through the trans-sulfuration pathway to produce cysteine and glutathione [8,9]. Methionine hydroxy analog free acid (MHA-FA) is chemically different from DL-Met because it has a hydroxyl group at the asymmetric carbon atom, whereas DL-Met has an amino group.…”
Section: Introductionmentioning
confidence: 99%
“…Because of deamination of other amino acids during conversion of D-Met to L-Met, different sources of methionine may perform differently. Ribeiro et al [8] observed that L-Met addition in broiler diet provided better FCR as compared to DL-Met, and MHA. Lui et al [15] observed that the bioavailability of MHA-FA was greater than DL-Met.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported methionine‐sparing effects of various micronutrients such as betaine, choline and other natural bioactive compounds . Ribeiro et al revealed the ability of broilers to utilize different forms and sources of methionine without compromising production performance …”
Section: Introductionmentioning
confidence: 99%
“…15,16 Ribeiro et al revealed the ability of broilers to utilize different forms and sources of methionine without compromising production performance. 17 Although extensive research has been conducted to evaluate the comparative efficiency of different synthetic sources of methionine, such as DLM and MHA, 4,9,17,18 studies regarding the biological efficacy of natural methionine compared with synthetic methionine are limited. Therefore an experiment was designed to compare relative bio-efficacies of natural methionine and synthetic methionine in broiler chicks.…”
Section: Introductionmentioning
confidence: 99%